Safeguarding Online Information against Failures and Attacks. - Liskov, Barbara (Communications of the ACM, 2008)
The article discusses safeguards taken for information that is stored online, especially safeguards that protect against attacks and system failures. Companies such as Google and Amazon offer to store information online, demonstrating that online information storage has become a commodity in 2008. Other topics include online information that can be shared with anybody, users who would not be satisfied if such information is not instantly accessible or lost, and data replication through the storage of information on multiple computers.